Benjamin Libet's experiment and its critique between 2000-2012 - Strzyżyński, Przemysław (Filozofia Chrześcijańska, 2013)
The article describes the results of Libet’s experiment and its resulting critique, as witnessed by the articles published between 2000 and 2012. As a result of his experiments, Libet concluded that conscious intentions of making a movement are preceded by brain activity registered as the readiness potentials (RP). In this interpretation, free will does not initiate the decision of making a move but is however capable of stopping this process. For this reason, Libet does not conclude that will is determined by biological processes. The resulting discussion in the literature concerns mainly methodology and conclusions drawn by Libet. The methodological points raised include an argument against the use of EEG as an accurate research tool and criticism of the method of timing the occurrence of the conscious intention of making a move. We note that subsequent modifications made to the original experiment, did however allow putting some of the methodological doubts to rest. On the other hand, the critique of Libet’s conclusions focuses on the problematic nature of correlation of physical movements with the readiness potentials. The most recent research also shows that the potentials might have a more complicated origin than previously thought. Libet’s interpretation is also criticised for its vagueness in defining intention and for not distinguishing it from wishes and desires. The last part of our article summarises the latest state of affairs as emerging from the analysis. We point out the difficulties in correlating potentials with movement, their interpretation and difficulties with the notion of veto, since it seems to require that contradictory intentions of making and refraining from a movement are present simultaneously. The article concludes that on the basis of the current research, the thesis about a biological determination of voluntary processes lacks a sound justification.